CHANGES IN ENZYME ACTIVITY IN LIVER CIRRHOSIS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Liver cirrhosis is a serious and potentially life-threatening condition that occurs when healthy liver tissue is replaced by scar tissue, leading to reduced liver function. One important aspect of diagnosing and monitoring liver cirrhosis is through the use of enzyme tests. In this article, we will explore the significance of enzyme diagnosis in the development of liver cirrhosis and how it plays a crucial role in managing this condition effectively.